The Influence of Affiliate Marketing and Content Reviews on the TikTok Application on the Consumptive Behavior of the New Generation of Indonesians (GenBI) in 11 Regions of North Sumatra - Aulia, Syaikah Nabilah; Lubis, Fauzi Arif; NUrbaiti, Nurbaiti (LP2M IAIN Palopo, 2025)
This study was conducted with the aim of determining the effect of Affiliate Marketing and Content Review on the TikTok application on the consumer behavior of the new generation of Indonesia (GenBI) 11 in the North Sumatra region. The type of research used is quantitative research. The population in this study were members of GenBI 11 in North Sumatra, consisting of 475 students from 8 universities, namely USU, UNIMED, UINSU, UMA, UNPAB, POLMED, UHN, and UMSU. From this population, the number of samples was determined using the Slovin formula in this quantitative study as many as 83 respondents with a purposive sampling technique. The data collection technique in this study used a questionnaire with a Likert measurement scale. The data analysis method used was multiple linear regression analysis using the Statistical Program for Social Science (SPSS). In this study, the results obtained were that Affiliate Marketing (X1) had a positive and significant influence on consumer behavior (Y), while Content Review did not have a significant influence on consumer behavior (Y). However, Affiliate Marketing (X1) and Content Review (X2) have a significant influence simultaneously on the consumer behavior (Y) of the New Generation of Indonesia (GenBI) 11 in the North Sumatra region.